THEORETICAL BASIS OF CUSTOMS CONTROL - Major I.D. Torakhodjhaeva (Scholar Express Journals, 2022)
The article examines the concept of customs control through the prism of the scientific direction of customs. Scientific opinions of researchers are stated, and also the author's definition of customs control is given.
Keywords: Customs law; customs control; customs system